(untitled) (International Journal of Engineering and Computer Science, 2017)
Emergency scenarios are very common in healthcare domain. These situations are very unpredictable and difficult to estimate the loss and amount of injuries or diseases that could occur. Hence it is impossible for the automated systems to detect these emergency situations and cannot provide the new information’s. In case of elderly persons and patients who reside at home, need to check their healthcare record periodically using the systems. At times this becomes time consuming and inefficient to use and it could also happen that the person may forget to record or monitor the values periodically. Another scenario to be considered is when the patient is alone and not able to communicate the emergency situation to the family members and doctors. Hence to help and identify this situation we propose a flexible access control framework using Complex Event Processing (CEP) technology. When an emergency is detected the temporary access control policies (tacps) will be activated. These control policies will override the regular policies in emergency cases.